2014
DOI: 10.3892/ol.2014.2828
|View full text |Cite
|
Sign up to set email alerts
|

Upregulation of the B7/CD28 family member B7-H3 in bladder cancer

Abstract: Abstract. Dysregulation of B7-H3 has been observed in a variety of types of human cancers. In the present study, the mRNA expression level of B7-H3 was analyzed in bladder cancer by performing semi-quantitative reverse transcription-polymerase chain reaction on clinical specimens from transitional cell carcinomas (TCCs) and their normal adjacent tissues (NATs).Immunohistochemical analysis was performed to compare the protein expression level of B7-H3 in TCCs and the paired NATs. The present study indicated tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 29 publications
(38 reference statements)
1
3
0
Order By: Relevance
“…A recent review summarized the expanding repertoire of potential targets for immune modulation in the bladder and pointed out CD276, HHLA2, and VTCN1 as such [15]. Our results corroborate this review as well as previous research showing the CD276 mRNA and protein are expressed in BLCA [16] and contribute to the accumulating evidence of its role in BLCA. CD276 expression promotes invasion and metastasis of urothelial cancer cells in vitro [17], and clinical trials with the anti-CD276 antibody MGA271 [18] are under way (www.clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 90%
“…A recent review summarized the expanding repertoire of potential targets for immune modulation in the bladder and pointed out CD276, HHLA2, and VTCN1 as such [15]. Our results corroborate this review as well as previous research showing the CD276 mRNA and protein are expressed in BLCA [16] and contribute to the accumulating evidence of its role in BLCA. CD276 expression promotes invasion and metastasis of urothelial cancer cells in vitro [17], and clinical trials with the anti-CD276 antibody MGA271 [18] are under way (www.clinicaltrials.gov).…”
Section: Discussionsupporting
confidence: 90%
“…Our previous study revealed that the cancer tissue from hepatocellular carcinoma (HCC) patients exhibited significantly increased levels of B7-H3 (10). B7-H3 has also been reported to be involved in the development of a variety of other solid tumor tissue cancer types, including osteosarcoma, pancreatic cancer, glioma, bladder cancer and non-small cell lung cancer (11)(12)(13)(14)(15), as well as in the development of inflammatory diseases (16).…”
Section: Introductionmentioning
confidence: 99%
“…In urothelial cancer of the bladder, preoperative bacillus Calmette-Guerin treatment is associated with B7-H3 overexpression [22]. Subsequent studies on urothelial cell tumors confirmed that B7-H3 overexpression is present in bladder tumors across all pathologic stages [22, 55] and is likely a consequence of increased B7-H3 mRNA expression in urothelial carcinoma cells [56]. …”
Section: New Immune Checkpoints B7-h3 B7x and Hhla2mentioning
confidence: 99%